Peculiarities of Electrodynamic Processes During Electric Explosion of Spiral Wires (London Journal of Research In Science: Natural and Formal, 2025)
The features of the electric explosion of spiral-shaped conductors in the RLC discharge circuit are considered. It has been experimentally established that during the explosion of spiral-shaped wires in water, in contrast to the explosion in air, the secondary breakdown occurs along the spiral ionized channel due to the greater density of the environment, the lower expansion rate of the explosion products, and the compressive effect of the discharge channel of its own magnetic field. The nature of the discharge process is determined by the increase in the active resistance of the spiral plasma channel during its expansion. Due to the additional action of magnetic pressure generated during the explosion of the spirals, the force effect on electrically conductive objects located inside or outside the spiral increases, which can be used when distributing pipes in tube grids and loading samples with high pulse pressure. In addition, when changing the initial parameters of the spirals (number of turns, pitch, diameter) during their explosion in water, in the discharge circuit it is possible to observe the nature of the discharge from deeply oscillatory to deeply aperiodic, including obtaining a single pulse of discharge current for its use as a breaker for high-power electrical circuits.
Keywords: pollution; Soil; heavy metals; Siret River sides